Influence of HEDPERF and Student Satisfaction against Perceived Service Value and Implications in Institutional Image - Mr Yusuf (Fakultas Ekonomi, Universitas Bangka Belitung, 2017)
This study aims to prove empirically the influence of HedPERF / service quality and student satisfaction on the value of service perceived by students and their implications on the image of UPBJJ-UT Pangkalpinang institution. Hypothesis testing, conducted on 238 students scattered in 7 districts/municipalities Kep. Bangka Belitung. The data used is the primary data from the distribution of questionnaires with 5 Likert scales. Data analysis using the quantitative method by using SEM analysis. Hedperf / service quality has a positive effect on student satisfaction, student satisfaction has a positive effect on the value of service perceived by students, and the value of service perceived by the students has a positive effect on the institutional image. While the HedPERF / negative service quality of each influence on the value of services perceived by students and the image of the institution and student satisfaction negatively impact on the image of the institution. Intervention variable testing, through student satisfaction positively mediates the influence of HedPERF / service quality on perceived service value and through perceived service value positively mediates the effect of student satisfaction on the institutional image. While through the perceived value of service and satisfaction of each student negatively mediate the influence of HedPERF / service quality on the institutional image.